2018
DOI: 10.1155/2018/5623683
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Effects of Binge Drinking Help in Its Detection and Differential Diagnosis from Alcohol Dependence

Abstract: The prevalence of binge drinking in the general population is 3-4 times higher than that of alcohol dependence. Neuroimaging studies show that binge drinking in adolescence impairs brain development and white matter integrity. Regions with reduced functional activity include the limbic system, ventral diencephalon, frontal lobe, and middle and inferior temporal lobes, whereas the right superior frontal and parietal lobes are typically hyperactivated. The observed activation of the frontoparietal areas might re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…Neighbors et al concluded that time-speci c calendar events [29] and event-speci c drinking [30] were associated with increased levels of bingeing. However, neurobiological changes may occur with repetitive binge-drinking conditions [31,32], and may increase cravings [33]. Ghiţă et al reported a variability of the levels of alcohol craving in relation to the day of the week, and drinking during weekends in Spain (Friday, Saturday, or Sunday) was associated with greater craving levels in patients with alcohol use disorder [17].…”
Section: Associations Between Dependence Signs and Increased Drinkingmentioning
confidence: 99%
“…Neighbors et al concluded that time-speci c calendar events [29] and event-speci c drinking [30] were associated with increased levels of bingeing. However, neurobiological changes may occur with repetitive binge-drinking conditions [31,32], and may increase cravings [33]. Ghiţă et al reported a variability of the levels of alcohol craving in relation to the day of the week, and drinking during weekends in Spain (Friday, Saturday, or Sunday) was associated with greater craving levels in patients with alcohol use disorder [17].…”
Section: Associations Between Dependence Signs and Increased Drinkingmentioning
confidence: 99%
“…The world's population of adults suffering from alcohol abuse is estimated at about 4.9%. More than 2% of the world's population is alcohol dependent, while in Europe, it is estimated at 4% and in America 3.4% [47]. The World Health Organization assessed that the problem of binge drinking concerns more than 7% of the world's population (over 16% in Europe and 13% in America).…”
Section: Alcohol Dependencementioning
confidence: 99%
“…The World Health Organization assessed that the problem of binge drinking concerns more than 7% of the world's population (over 16% in Europe and 13% in America). In the last years, binge drinking has become the dominant pattern of alcohol consumption among adults [47].…”
Section: Alcohol Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Proton magnetic resonance spectroscopy ( 1 H MRS) is a useful tool that detects brain metabolites such as NAA (N-acetylaspartate), a marker for neuronal integrity or neuronal-glial homeostasis; Glx (GABA, glutamine, and glutamate); Cho (choline containing compounds), a measure of cellular density; Cr (creatine plus phosphocreatine), a marker of cellular energy level; and mI (myo-inositol), a marker of brain osmotic balance and glial cells [5, 6]. It is known that not only MRI brain imaging or neurophysiological measures but also the neurochemical changes detected by MRS may be biomarkers of schizophrenia and other neuropsychiatric disorders, e.g., posttraumatic stress disorder, antidepressant treatment response, or binge drinking [710].…”
Section: Introductionmentioning
confidence: 99%